Analysis of combined cooling heating and power generation from organic Rankine cycle and absorption system - Nattaporn Chaiyat (2018)
© 2015 Elsevier Ltd. This paper focuses on the feasibilities of energy, economic and environment of a method to enhance an ORC (organic Rankine cycle) efficiency by CCHP (combined cooling heating and power) generation from an absorption system for reducing the ORC condenser temperature. A projection of a 25 kWeR245fa ORC integrated with a 20 kW LiBr-water absorption unit was considered. The experimental data of both units were generated as performance curves and used to find out the suitable operating conditions. It could be found that the ORC with the absorption system gave higher total efficiency compared with the normal ORC. The ORC efficiency could be increased around 7%, with 15 °C of cooled water temperature supplied from the absorption system. But, in term of the economic result, a LEC (levelized electricity cost) of the modified system was around 0.0891 USD/kWh, which was higher than that of the normal system at around 0.0669 USD/kWh. In term of the environmental impact, a released carbon dioxide intensity of the new unit was lower than the normal unit at around 0.203 and 0.216 kg CO2eq/kWh, respectively.